Endobronchial squamous cell carcinoma presenting as localized, long, continuous bronchial thickening on CT. Issue 91 (June 2017) - Song, Yoonah; Choi, Yo Won; Paik, Seung Sam; Han, Dae Hee; Lee, Kyo Young
Abstract: Objective: To report pulmonary squamous cell carcinomas presenting as localized, long, continuous, bronchial thickening on computed tomography (CT). Materials and methods: This study comprised five men (mean age, 66 years; range, 60–79 years) with pulmonary squamous cell carcinoma, including two (0.6%) selected from 310 consecutive patients with the diagnosis. Inclusion criteria were as follows: histological diagnosis obtained from thickened bronchi; continuous bronchial thickening > 5 cm in longitudinal extension on CT. CT scans were retrospectively reviewed, focusing on bronchial abnormalities. They were correlated with histopathological findings in four patients who underwent lobectomy. Results: On initial CT, bronchial thickening was continuous without skip area (n = 5), measured 56–114 mm in maximum longitudinal length, involved lobar (n = 3) or segmental and distal bronchi (n = 5) of the right upper (n = 4) or lower (n = 1) lobe, and was focally bulbous (n = 2). Follow-up CT before treatment, available in two, showed progression of bronchial thickening in its thickness and longitudinal length (n = 2) and a new bulbous portion (n = 1) and peribronchial nodules (n = 1) along the thickened bronchi. Cancer recurred after lobectomy in two, one of which manifested as continuous bronchial thickening extending from the bronchial stump on CT. On CT-histopathological correlation, bronchial thickening was mostly due to tumor spreading along the bronchus. A focal or short segmental tumor outgrowth from the thickened bronchi corresponded to a nodule or bulbous portion along thickened bronchi on CT, respectively. Conclusion: Pulmonary squamous cell carcinoma may present as localized, long, continuous, bronchial thickening on CT, simulating benign infectious or inflammatory diseases.